2017
DOI: 10.1080/10717544.2016.1267275
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of isoniazid and rifampin in guinea pigs by electro-phonophoresis

Abstract: Electro-phonophoresis (EP) has been used as a drug delivery approach in clinical fields. The objective of the present study is to evaluate the skin permeability of isoniazid and rifampin in guinea pigs by EP to provide reference basis for clinical applications of such transdermal delivery system in the treatment of patients with superficial tuberculosis. Isoniazid and rifampin solutions were delivered transdermally with or without EP in health guinea pigs for 0.5 h. Local skin and blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Previous studies evaluated the transdermal delivery of INH/RIF and reported avoidance of the hepatic first-pass effect, which resulted in dose reduction and mitigation of side effects (peripheral neuropathy and hepatotoxicity). 10,12 Chen et al investigated transdermal delivery of RIF and INH using electro-phonophoresis for treatment of superficial skin tuberculosis and tubercular lymphadenitis. 12 However, these drugs were evaluated as components of a nanocarrier-based transdermal delivery system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies evaluated the transdermal delivery of INH/RIF and reported avoidance of the hepatic first-pass effect, which resulted in dose reduction and mitigation of side effects (peripheral neuropathy and hepatotoxicity). 10,12 Chen et al investigated transdermal delivery of RIF and INH using electro-phonophoresis for treatment of superficial skin tuberculosis and tubercular lymphadenitis. 12 However, these drugs were evaluated as components of a nanocarrier-based transdermal delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 Chen et al investigated transdermal delivery of RIF and INH using electro-phonophoresis for treatment of superficial skin tuberculosis and tubercular lymphadenitis. 12 However, these drugs were evaluated as components of a nanocarrier-based transdermal delivery system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…INH gets converted to isonicotinic acid due to radicalmediated chain reaction (Bhutani et al).It comes under borderline of BCS Class I and Class III drugs with good aqueous solubility of (140000 mg/L at 25°C), Log P -0.71(hansch, ceta1995) and pKa of 1.82 at 20°C (Perrin, DD 1965). It is a bactericidal drug and acts by inhibiting biosynthesis of mycolic acid which is major component of bacterial cell wall 6 . The drug faces various stability problems like hydrolysis, oxidation and photolysis, forming isonicotinic acid and isonicotinamide.…”
Section: Mycobacteriummentioning
confidence: 99%